Pengembangan Media Ular Tangga Berbasis Augmented Reality untuk Meningkatkan Hasil Belajar IPAS Sekolah Dasar - Ristiani, Rima; Faturrahman, Moh. (Universitas Muhammadiyah Magelang, 2026)
This research is driven by the limited application of technology-based learning media in social studies education in elementary schools, which results in decreased student engagement and learning outcomes. This study aims to design an Augmented Reality-based snakes and ladders game media and evaluate its feasibility and effectiveness in improving the learning outcomes of fifth-grade elementary school students regarding the diversity of flora and fauna in Indonesia. The methodology used is Research and Development (R&D) using the Borg and Gall model, which includes phases such as needs assessment, product design, expert validation, revision, and product trials. The research participants consisted of fifth-grade elementary school students involved in small-scale and large-scale trials. Data collection methods include observation, interviews, expert validation questionnaires, and assessment of learning outcomes through pretest and posttest instruments. The results showed that the media achieved a very feasible classification based on validation by media experts (93.75%) and subject matter experts (87.5%). Statistical analysis showed a significant difference between pretest and posttest scores (significance <0.05), as well as a high category of N-Gain values ​​in both small-scale and large-scale trials. Therefore, the snakes and ladders game media based on Augmented Reality has proven effective as an innovative educational alternative to improve science learning outcomes among elementary school students.